Access to Justice For Vulnerable Groups In Law - Hijriani, Hijriani; Hasima , Rahman (International Journal of Management and Education in Human Development, 2022)
Indonesia is facing difficulties in providing particular protection to vulnerable groups who require the same level of protection and access to justice as the rest of society. This research intends to 1) understand the government's perspective in establishing policies, such as laws and regulations, that provide vulnerable groups with equal protection under the law and access to justice; and 3) challenges in providing protection for vulnerable groups. This study employs a normative legal research method that includes both an analytical and a statute-based approach. The following are the outcomes of this study's discussion: 1). The Indonesian government has established several national policies and regulations, including the National Strategy for Access to Justice (SNAK) 2016-2019, various regulations regarding the requirements and procedures for providing legal aid, and in the judicial system, the Supreme Court has enacted several regulations aimed at increasing access to justice for vulnerable groups. According to the Supreme Court, the state still has numerous obstacles in providing special protection to vulnerable groups such as children, women, people with disabilities, believers, and other minorities.